RUSSIA IN A SEARCH OF OPTIMAL STRATEGY FOR POST-SOVIET INTEGRATION: WILL THE YEAR 2012 BE A TURNING POINT? - A. G. Bolshakov (Сравнительная политика, 2015)
The article is devoted new integration projects in adjacent territories with Russia which are realized and discussed at the moment on the post-Soviet territory. After twenty years of postsocialist development the potential of the CIS is still unknown, debatable widely advertized project of the Eurasian union is represented. The regionalization of the post-Soviet territory and local integration Russian projects are realities of the present stage of development of the former territory of the USSR. Dominating here in the economic and political plan the Russian Federation can choose various variants of integration and cooperation, including with the states which weren’t components of Soviet Union. The Russian elite has counted on development of the national interests including various integration projects on the post-Soviet territory, and uses idea of a reconstruction of the USSR as one of ideologem, for attraction on the party of the citizens professing traditional Soviet values.